2021
DOI: 10.3389/fendo.2021.722586
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Variety of Immune-Related Adverse Events Triggered by Immune Checkpoint Inhibitors in a Subject With Malignant Melanoma: Destructive Thyroiditis, Aseptic Meningitis and Isolated ACTH Deficiency

Abstract: Recently, immune checkpoint inhibitors have been drawing much attention as cancer immunotherapy, but it has been shown that various immune-related adverse events (irAEs) are induced by immune checkpoint inhibitors in various organs, which has become one of the serious issues at present. A 58-year-old Japanese male with malignant melanoma was treated with nivolumab and/or ipilimumab. During the period of treatment, he suffered from various irAEs. Firstly, about 1 month after starting nivolumab monotherapy, dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, as stated earlier, Mikami et al described an incidence as high as 5.3% with anti-PD-L1 inhibitors, suggesting that this condition is becoming more common, especially with the rise of immune therapy 3. Not only neurological irAEs have been reported in the literature, but also endocrinopathies such as hypopituitarism and adrenal cortex dysfunction 6…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, as stated earlier, Mikami et al described an incidence as high as 5.3% with anti-PD-L1 inhibitors, suggesting that this condition is becoming more common, especially with the rise of immune therapy 3. Not only neurological irAEs have been reported in the literature, but also endocrinopathies such as hypopituitarism and adrenal cortex dysfunction 6…”
Section: Discussionmentioning
confidence: 90%
“…Regarding the treatment of irAEs, steroids have been proposed with a dose of prednisone of 1 mg/kg/day. We did not use steroids for this patient due to spontaneous clinical improvement, but a similar case used intravenous prednisolone (1 mg/kg/day), achieving rapid clinical improvement 6. Shields et al state treatment plans can also include high-dose corticosteroids as well as intravenous immunoglobulins (IVIGs) and plasmapheresis in severe cases 11.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 11 articles, 40 cases of immune-related meningitis or meningoencephalitis (with at least signs of meningitis on lumbar puncture) were reported [10][11][12][13][14][15][16][17][18][19][20][21][22] (Tables 1 and 2). An overview of the results is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…New irAEs were reported in three patients after reintroduction, all of whom had received the same ICI. One patient developed interstitial lung disease and meningitis relapse, and the other two developed adrenal insufficiency [11,21,28]. Takamasu et al reported that a patient with stage IV renal cell carcinoma achieved a complete response owing to the combination of ipilimumab 1 mg/kg and nivolumab 3 mg/kg, despite irAE reoccurrence [28].…”
Section: Follow-up and Therapy Reintroductionmentioning
confidence: 99%